The Challenge of Scientometrics. The Development, Measurement, and SelfOrganization of Scientific Communications - Léa Velho (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2015)
Universal Publishers / uPUBLISH.com, 2001 ISBN: 1-58112-681-6